Epilepsy and cannabidiol: a guide to treatment. Issue 1 (13th March 2020) - Arzimanoglou, Alexis; Brandl, Ulrich; Cross, J. Helen; Gil‐Nagel, Antonio; Lagae, Lieven; Landmark, Cecilie Johannessen; Specchio, Nicola; Nabbout, Rima; Thiele, Elizabeth A.; Gubbay, Oliver; ,
ABSTRACT: The growing interest in cannabidiol (CBD), specifically a pure form of CBD, as a treatment for epilepsy, among other conditions, is reflected in recent changes in legislation in some countries. Although there has been much speculation about the therapeutic value of cannabis‐based products as an anti‐seizure treatment for some time, it is only within the last two years that Class I evidence has been available for a pure form of CBD, based on placebo‐controlled RCTs for patients with Lennox‐Gastaut syndrome and Dravet syndrome. However, just as we are beginning to understand the significance of CBD as a treatment for epilepsy, in recent years, a broad spectrum of products advertised to contain CBD has emerged on the market. The effects of these products are fundamentally dependent on the purity, preparation, and concentration of CBD and other components, and consensus and standardisation are severely lacking regarding their preparation, composition, usage and effectiveness. This review aims to provide information to neurologists and epileptologists on the therapeutic value of CBD products, principally a purified form, in routine practice for patients with intractable epilepsy.